The Influence of Specialist Development Education and Work Involvement on Personnel Performance of the Water Patrol Sub-Directorate of Water Police, Republic of Indonesia Police Headquarters - Wigiantoro, Dimas Bangkit; Pratikno, Yuni; Hanaffy, Jamal (Dinasti International Journal of Digital Business Management, 2026)
Personnel performance is a crucial factor in supporting the effectiveness of police operational tasks, particularly in the Water Patrol Subdirectorate of the Water Police Directorate of the Indonesian National Police Headquarters, which has high-risk task characteristics and requires special competencies. This study aims to analyze the influence of specialist development education and work engagement on personnel performance, both partially and simultaneously. This study uses a quantitative approach with the aim of examining the relationship between variables objectively and measurably through numerical data. To enrich the understanding of empirical conditions in the field, this study is also supplemented with qualitative data in the form of statements in questionnaires, consultation results, and brief interviews with informants. The study population consisted of 104 personnel of the Water Patrol Subdirectorate of the Water Police Directorate of the Indonesian National Police Headquarters, and the entire population was used as respondents through a total sampling technique. Hypothesis testing was conducted using multiple linear regression analysis with the help of SPSS version 29 software. The results of the study indicate that specialist development education partially has a positive and significant effect on personnel performance. Similarly, work engagement is proven to have a positive and significant effect on personnel performance. Simultaneously, both variables contribute significantly to improving personnel performance. The coefficient of determination (R Square) value of 0.432 indicates that specialist development education and work engagement are able to explain 43.2% of the variation in personnel performance, while the remaining 56.8% is influenced by other factors outside the research model. This finding confirms that improving the quality of relevant specialist education and strengthening personnel work engagement are important strategies in improving personnel performance at the Water Patrol Sub-Directorate of the Water Police Directorate of the Indonesian National Police Headquarters